Effects of protein hydrolysates supplementation in low fish meal diets on growth performance, innate immunity and disease resistance of red sea bream Pagrus major. Issue 2 (August 2015) - Khosravi, Sanaz; Rahimnejad, Samad; Herault, Mikaël; Fournier, Vincent; Lee, Cho-Rong; Dio Bui, Hien Thi; Jeong, Jun-Bum; Lee, Kyeong-Jun
Abstract This study was conducted to evaluate the supplemental effects of three different types of protein hydrolysates in a low fish meal (FM) diet on growth performance, feed utilization, intestinal morphology, innate immunity and disease resistance of juvenile red sea bream. A FM-based diet was used as a high fish meal diet (HFM) and a low fish meal (LFM) diet was prepared by replacing 50% of FM by soy protein concentrate. Three other diets were prepared by supplementing shrimp, tilapia or krill hydrolysate to the LFM diet (designated as SH, TH and KH, respectively). Triplicate groups of fish (4.9 ± 0.1 g) were fed one of the test diets to apparent satiation twice daily for 13 weeks and then challenged by Edwardsiella tarda. At the end of the feeding trial, significantly (P < 0.05) higher growth performance was obtained in fish fed HFM and hydrolysate treated groups compared to those fed the LFM diet. Significant improvements in feed conversion and protein efficiency ratios were obtained in fish fed the hydrolysates compared to those fed the LFM diet. Significant enhancement in digestibility of protein was found in fish fed SH and KH diets and dry matter digestibility was increased in the group fed SH diet in comparison to LFM group. Fish fed the LFM diet showed significantly higher glucose level than all the other treatments. Whole-body and dorsal muscle compositions were not significantly influenced by dietary treatments. Histological analysis revealed significant reductions in goblet cell numbers and enterocyte length in the proximal intestine of fish fed the LFM diet. Superoxide dismutase activity and total immunoglobulin level were significantly increased in fish fed the diets containing protein hydrolysates compared to the LFM group. Also, significantly higher lysozyme and antiprotease activities were found in fish fed the hydrolysates and HFM diets compared to those offered LFM diet. Fish fed the LFM diet exhibited the lowest disease resistance against E. tarda and dietary inclusion of the hydrolysates resulted in significant enhancement of survival rate. The results of the current study indicated that the inclusion of the tested protein hydrolysates, particularly SH, in a LFM diet can improve growth performance, feed utilization, digestibility, innate immunity and disease resistance of juvenile red sea bream.